THE EFFECT OF SOLID MATERIAL VARIATION ON THE SPREADING BEHAVIOR OF SINGLE DROPLET IMPINGIMENT ONTO AN INCLINED HEATED SURFACE - Rio Budiman; Indarto Indarto; Deendarlianto Deendarlianto; Teguh Wibowo (Lembaga Penelitian Universitas Trisakti, 2020)
Single droplet impingement onto an inclined heated surface was studied experimentally. The droplet was dropped from 70 mm fixed height to the material surface with a 45º impact angle. The experiment used three types of materials; Stainless Steel AISI 304, Aluminum Alloy 2024, and Copper. Each test material has average surface roughness, Ra 0.06 μm. Materials are assumed to have the same surface treatment condition. Droplet behavior observed at surface temperatures of 100 ºC and 140 ºC. Droplet has a 3.0 mm diameter and 28.5 Weber number (low impact category). A high-speed camera 4000 fps (frames per second) with image resolution 1024 x 768 was used to analyze the droplet behavior after impact. MATLAB image processing technique used to determine the spreading ratio and dimensionless height. The results showed that the droplets have different behavior even at the same surface temperature. Boiling regimes influence both spreading and dimensionless height ratios. In the natural convection regime, the oscillation of the spreading droplet ratio influenced by Weber number and gravity. During the nucleate boiling and at Leidenfrost temperature, the spreading ratio influenced by bubble growth and secondary atomization.